2024
DOI: 10.1109/ojemb.2023.3267726
|View full text |Cite
|
Sign up to set email alerts
|

Voxel-Wise Brain Graphs From Diffusion MRI: Intrinsic Eigenspace Dimensionality and Application to Functional MRI

Abstract: Structural brain graphs are conventionally limited to defining nodes as gray matter regions from an atlas, with edges reflecting the density of axonal projections between pairs of nodes. Here we explicitly model the entire set of voxels within a brain mask as nodes of high-resolution, subject-specific graphs. Methods: We define the strength of local voxel-to-voxel connections using diffusion tensors and orientation distribution functions derived from diffusion MRI data. We study the graphs' Laplacian spectral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
1
4
0
Order By: Relevance
“…Qualitatively, we found that the lowest harmonics in the consensus SC matched with those previously reported [61, 33, 5] (Figure 1A). Quantitatively, we investigated how SC harmonics related to spatial frequency properties; namely sparsity, zero-cross rate, network zero-crossings [23], and roughness.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Qualitatively, we found that the lowest harmonics in the consensus SC matched with those previously reported [61, 33, 5] (Figure 1A). Quantitatively, we investigated how SC harmonics related to spatial frequency properties; namely sparsity, zero-cross rate, network zero-crossings [23], and roughness.…”
Section: Resultssupporting
confidence: 90%
“…Note that others have recently performed eigenvector alignment using Procrustes [5]; however, we refrained from this approach to preserve as much of the subject-specific features in the harmonics as possible, since understanding the subtle harmonic variation across subjects is a key question evaluated in this work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through a series of experiments, we show the superiority of the proposed method over conventional strategies of performing classification based on correlation-based FC. Our promising results suggest the potential to further expand the proposed MTNN architecture, to take as input higher resolution FC graphs [23] or fMRI spectral features extracted on atlas-based [24] or high resolution [25,26] structural brain graphs. Lastly, a detailed analysis of the significance of intra/inter network connections in the performance of the trained models is a fertile avenue for future research.…”
Section: Discussionmentioning
confidence: 93%
“…To this end, we used the Procrustes transform (PT) 36 , which finds the optimal rotation to match two linear subspaces. This method has been previously used in related work 37 , albeit with a different goal, to quantify the degree of inter-subject variability of eigenmodes of voxel-wise brain graphs. Given two sets of K eigenmodes, PT optimally transforms one set to match the other set.…”
Section: Supplementary Materialsmentioning
confidence: 99%